Karakteristik Marshall pada Campuran Aspal HRS-WC Menggunakan Abu Sekam Padi - Hermansyah Hermansyah; Arif Fajar Isnan; Febri Yanti (Jurnal Manajemen Teknologi & Teknik Sipil, 2022)
Poor flexible pavement and not accordance with specifications can cause bumpy roads, potholes, and allow accidents to occur. For this reason, special attention is needed in designing and making asphalt mixtures. One type of asphalt mixture is the Hot Rolled Sheet Wearing Course (HRS-WC). The purpose of this study was to determine the marshall characteristics of the HRS-WC asphalt mixture with rice husk ash as filler. The research was conducted by making normal test objects and with rice husk ash filler. Furthermore, Marshall testing and analysis were carried out including void values, stability, flow, marshall quotient, and residual marshall. The results of this analysis are then compared with the reference standard HRS-WC asphalt mixture in the 2018 General Specification revision 2. The results of this research are the most optimum mixture variation level at 1.8% which can increase the value of voids in the mixture and voids filled with asphalt, while the value of voids in the aggregate, marshall stability, marshall quotient, flow and residual marshall decreased. The characteristic values for the 1.8% mixture variation, among others, the voids in the mixture are 3.66%, the voids in the aggregate are 21.21%, the voids filled with asphalt are 82.75%, the marshall stability is 639 kg, the flow is 3 .05 mm, the marshall quotient is 209 kg/mm and the remaining marshall is 92.56%. So that the results of this research can be used as a reference for researchers and the general public in determining the filler in the HRS-WC asphalt mixture.